Experimental and mathematical survey of sound absorption performance of date palm fibers. Issue 6 (June 2019) - Taban, Ebrahim; Khavanin, Ali; Jafari, Ahmad Jonidi; Faridan, Mohammad; Tabrizi, Ali Kazemi
Abstract: The present study examines the acoustic behavior sample composites made of date palm natural fibers and polyvinyl alcohol. It also provides the comparison between the sound absorption coefficients obtained from the experimental tests and the ones predicted by the mathematical models. An impedance tube system was used to measure the normal sound absorption coefficient of the samples. Using the differential equation algorithm, the predicted sound absorption coefficient for the Johnson-Champoux-Allard model was also calculated. The sound absorption properties of samples increased significantly by increasing the frequency, and increasing the thickness of materials with constant density. Comparison of the data from the experimental tests and mathematical model showed that increasing the thickness of samples will make the predicted and tested values of acoustic absorption coefficient significantly comparable. Date palm fibers have a good potential for dissipating the energy of sound waves particularly when an air gap is introduced behind the sample and can be used as a new source for the fabrication of natural fiber reinforced composites.